2019
DOI: 10.1136/neurintsurg-2018-014569
|View full text |Cite
|
Sign up to set email alerts
|

European Stroke Organisation (ESO) - European Society for Minimally Invasive Neurological Therapy (ESMINT) Guidelines on Mechanical Thrombectomy in Acute Ischemic Stroke

Abstract: BackgroundMechanical thrombectomy (MT) has become the cornerstone of acute ischemic stroke management in patients with large vessel occlusion (LVO).ObjectiveTo assist physicians in their clinical decisions with regard toMT.MethodsThese guidelines were developed based on the standard operating procedure of the European Stroke Organisation and followed the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) approach. An interdisciplinary working group identified 15 relevant questions, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
182
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 283 publications
(197 citation statements)
references
References 147 publications
(176 reference statements)
4
182
1
10
Order By: Relevance
“…31,32 In addition, our findings contradict a recent report from Australia showing higher rates of clot migration to distal (M2, M3, and beyond) middle cerebral artery branches prior to the onset of MT with IVT pretreatment. 33 In view of the former considerations, we consider that our findings lend support to current international recommendations advocating that all tPA-eligible LVO 34,35 Compared to the previously published meta-analyses, our report includes a significantly higher number of studies, patients, and outcomes ( Supplementary Table 27). Moreover, our meta-analysis is the first to provide associations that have been adjusted for potential confounders in the majority of included studies.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…31,32 In addition, our findings contradict a recent report from Australia showing higher rates of clot migration to distal (M2, M3, and beyond) middle cerebral artery branches prior to the onset of MT with IVT pretreatment. 33 In view of the former considerations, we consider that our findings lend support to current international recommendations advocating that all tPA-eligible LVO 34,35 Compared to the previously published meta-analyses, our report includes a significantly higher number of studies, patients, and outcomes ( Supplementary Table 27). Moreover, our meta-analysis is the first to provide associations that have been adjusted for potential confounders in the majority of included studies.…”
Section: Discussionsupporting
confidence: 75%
“…We also documented no increase in the risk of post-MT complications (any ICH, groin hematoma, distal embolization, infarct in new vessel territory) for BT compared to dMT. 34,35 Compared to the previously published meta-analyses, our report includes a significantly higher number of studies, patients, and outcomes (Supplementary Table 27). Our findings provide evidence against the theoretical concerns of increased intracranial and extracranial bleeding risk with IVT pretreatment.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,28 In the European Stroke Organization (ESO)-ESMINT guidelines published in 2019, there was a consensus that mechanical thrombectomy would be reasonable for patients with M2 occlusion. 29 Use of direct aspiration in these territories may have the advantage of not crossing the occlusion and could be safer than stent retrievers. 30 It has also been suggested that aspiration has the potential for less endothelial damage.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Large vessel occlusion (LVO) is the most severe type of ischemic stroke, with the highest disability and mortality. 8,9 However, the guidelines do not mention MT for LVO patients with renal dysfunction. [3][4][5][6][7] Current guidelines state that patients with LVO stroke should be treated with MT as soon as possible.…”
Section: Introductionmentioning
confidence: 99%
“…MT is recommended for patients within 6 hours of anterior circulation occlusion, 6-24 hours of anterior circulation occlusion after strict imaging screening, and within 24 hours of posterior circulation vascular occlusion. 8,9 However, the guidelines do not mention MT for LVO patients with renal dysfunction. A study has shown that patients with cardiogenic stroke combined with impaired renal function have worse outcomes than those with cardiogenic stroke alone.…”
Section: Introductionmentioning
confidence: 99%